1999
DOI: 10.1515/hf.1999.007
|View full text |Cite
|
Sign up to set email alerts
|

Acid Reactions of Lignin Models of β-5 Type

Abstract: IntroductionDehydrodiconiferyl alcohol (1) is obtained in moderate yield on oxidation of coniferyl alcohol (Freudenberg and Hübner 1952). Catalytic hydrogenation of 1 gives the dihydro derivative 2. This latter compound has frequently been used as a model compound representative of β-5 structures of the phenylcoumaran type (3) in lignins. Refluxing of 2 with 0.2M HCl in dioxane-water (9 : 1) gives the phenylcoumarone 4 (Adler and Lundquist 1963) (Fig. 1). Compound 4 exhibits a strong absorbance in the UV regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…The β-5 linkage is almost exclusively modified via a similar mechanism. [17] This also means, that the formaldehyde released during these reactions is probably trapped in the form of its ethylene-glycol acetal 1,3-dioxolane as also confirmed in our earlier studies.…”
Section: Resultssupporting
confidence: 80%
“…The β-5 linkage is almost exclusively modified via a similar mechanism. [17] This also means, that the formaldehyde released during these reactions is probably trapped in the form of its ethylene-glycol acetal 1,3-dioxolane as also confirmed in our earlier studies.…”
Section: Resultssupporting
confidence: 80%
“…50 Meanwhile, β−5 units could be converted to stilbenes through loss of the γ-methylol group as formaldehyde. 52 Although complete removal of β−O−4 interlinkages in lignin could be achieved under conventional organosolv pretreatments at harsh pretreatment conditions, 53 one of the advantages of using THF as the water cosolvent is that THF could preferentially solvate lignin and the THF/water cosolvent mixture could act as a "theta" solvent to prevent lignin aggregation or repolymerization while facilitating lignin solubilization. 34 GPC results indicated that CELF lignin had much lower weight-average molecular weight (M w ) and number-average molecular weight (M n ) compared to CEL, suggesting significant lignin depolymerization during CELF pretreatment.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…In summary, the formation of 1,3-dioxane structures 1 and phenyl-dihydrobenzofuran 3 from GG under the acidic GVL-H 2 O system suggests that the actions of GVL pretreatment on lignin model GG was different from those induced by the traditional acidolysis. [18][19][20][21]. In the acidic GVL-H 2 O system used here, compound 22 was transformed following the pathway described in Figure 5.…”
Section: Reactions Of β-O-4 Lignin Model Gg In Gvl/ H 2 O (80/20) Systemmentioning
confidence: 99%
“…The β-5 (phenylcoumaran) types of structures are the second most abundant component of lignin. The reactions of β-5 lignin model compounds 22 and 26 have been investigated under acidolysis conditions [18][19][20][21]. In the acidic GVL-H2O system used here, compound 22 was transformed following the pathway described in Figure 5.…”
Section: Reactions Of β-5 Lignin Models In Gvl/ H2o (80/20) Systemmentioning
confidence: 99%
See 1 more Smart Citation